2018
DOI: 10.2741/4650
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical interaction of resveratrol with sirtuin pathway Significance in Alzheimer rsquo s disease

Abstract: Alzheimer disease (AD) is a widespread neurodegenerative condition that leads to progressive cognitive dysfunction in elderly population. Despite several attempts aimed at molecular determinants of AD, effective disease modifying treatment options are highly limited. Recently, use of natural supplements has gained considerable attention in AD research due to their cost effective and long lasting health beneficial properties. Resveratrol (RSV) is a naturally occurring polyphenolic compound found majorly in grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Increase in the SOD activity may reduce the lipid peroxidation (Abdel-Hafez et al 2010 ) and estimation of its activity and its relation with the lipid peroxidation could help the clinicians in understanding the prognosis of the neuronal damage and to plan the treatment, accordingly. Since oxidative stress has an evidence in the pathophysiology of AD, there are several studies which have been conducted and they supported the therapeutic efficacy of the antioxidant components in the AD (Park et al 2008 ; Mohan et al 2018 ; Gomes et al 2018 ). Extrapolating this phenomenon, the polyphenolic compounds found in the plants, which reduce the oxidative stress in these plants would provide the antioxidant support in human brain as well.…”
Section: Introductionmentioning
confidence: 99%
“…Increase in the SOD activity may reduce the lipid peroxidation (Abdel-Hafez et al 2010 ) and estimation of its activity and its relation with the lipid peroxidation could help the clinicians in understanding the prognosis of the neuronal damage and to plan the treatment, accordingly. Since oxidative stress has an evidence in the pathophysiology of AD, there are several studies which have been conducted and they supported the therapeutic efficacy of the antioxidant components in the AD (Park et al 2008 ; Mohan et al 2018 ; Gomes et al 2018 ). Extrapolating this phenomenon, the polyphenolic compounds found in the plants, which reduce the oxidative stress in these plants would provide the antioxidant support in human brain as well.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that RES has different therapeutic efficacies, like modulation of many cell‐signalling pathways [ 35 ], antioxidant, anti‐ageing attributes [ 36 ], anti‐inflammatory, anticancer [ 37 ], and neuroprotective (such as AD and PD) [ 38 ]. Studies have shown that RES as a polyphenolic stilbene supplement is involved in various pathophysiological functions of AD [ 39 , 40 ]. According to the chemical and physical properties and the mechanism of its interaction with extracellular and intracellular molecules, RES has anti‐amyloidogenic properties and can be promising against neuroinflammation and inhibition of AD [ 41 ].…”
Section: Resveratrolmentioning
confidence: 99%
“…The potential capability of RES stimulates the dephosphorylation of the microtubule‐dependent P‐Tau via the inhibition of GSK‐3β and calcium/calmodulin‐dependent protein kinase II (CaMKII) [ 100 ], and the gene overexpression of Sirt1 induces the deacetylation of acetylated Tau [ 101 ]. The investigations offer that RES could boost cognitive action in the senile, induce neuroplasticity, and enhance brain‐derived growth factor via activation of the Sirt1/AMPK pathway in the adult brain [ 39 , 48 ]. The results of Sirt1 upregulation by RES can prevent neuronal cell death by deacetylating p53, NF‐κB, and Forkhead box O, there preventing Aβ accumulation and neurodegeneration in AD [ 102 , 103 ].…”
Section: Resveratrolmentioning
confidence: 99%